Relationship between Body Habitus and Aggression Subtypes among Healthy Young Adults from the American Midwest. Issue 9 (20th October 2020) - Hartin, Samantha N.; Hossain, Waheeda A.; Manzardo, Ann M.; Brown, Shaquanna; Fite, Paula J.; Butler, Merlin G.
ABSTRACT: This study examined associations between body habitus and functions of aggression, in a sample of 474 college students from the Midwestern region of the United States (age range = 18-25y; 73% Caucasian). Two instruments of aggression, the Reactive-Proactive Aggression Questionnaire from Dodge & Coie (DC) and Raine et al. (RPQ) were given as self-assessments. Body habitus measures standardized by age and gender specific weight and height were collected. Subjects considered to have a large body habitus in our study had both weight and height measures above the 75th percentile. Large body habitus was positively correlated with both proactive and reactive functions of aggression among adult males but not females; however, regression analyses indicated that body habitus was most strongly and robustly associated with proactive aggression. Findings suggest that even in a healthy homogeneous population, large body size in males is associated with aggression, particularly proactive aggression including bullying rather than retaliatory aggression. The presence of a large body physique may reinforce aggressive behavioral traits acquired through life experiences and activities evoking physical dominance. Alternatively, the relationship may reflect neurological processes related to size influenced by genetic factors and hormones leading to antisocial behaviors requiring future research on the role of genes for aggression.